Professional behavior among dental students: Role of self and peer assessment in improving student performance - John, Jacob; Saub, Roslan; Mani, Shani Ann; Elkezza, A.; Malhotra, Vaishali (2017)
The aim of the study is to determine if the self- (SAP) and peer-assessment process (PAP), used early in the dental clinical curriculum, can serve as a useful tool to assess and provide feedback regarding professional behavior of dental students.